Expression of MicroRNAs in the Eyes of Lewis Rats with Experimental Autoimmune Anterior Uveitis - Yung-Ray Hsu; Shu-Wen Chang; Yu-Cheng Lin; Chang-Hao Yang (Hindawi Limited, 2015)
Purpose. This study aimed to determine the dynamic changes of NF-κB-related microRNAs (miRNAs) and cytokines over the course of experimental autoimmune anterior uveitis (EAAU) and elucidate the possible immunopathogenesis. Materials and Methods. Uveitis was induced in Lewis rats using bovine melanin-associated antigen. The inflammatory activity of the anterior chamber was clinically scored, and leukocytes in the aqueous humor were quantified. RNA was extracted from the iris/ciliary bodies and popliteal lymph nodes to reveal the dynamic changes of eight target miRNAs (miR-155-5p, miR-146a-5p, miR-182-5p, miR-183-5p, miR-147b, miR-21-5p, miR-9-3p, and miR-223-3p) and six cytokine mRNAs (IFN-γ, IL-17, IL-12A, IL-1β, IL-6, and IL-10). In situ hybridization of miRNA and enzyme-linked immunosorbent assay quantification of cytokines were performed to confirm the results. Results. Disease activity and leukocyte quantification were maximum at day 15 after immunization. The profiling of miRNA revealed downregulation of miR-146a-5p, miR-155-5p, miR-223-3p, and miR-147b and upregulation of miR-182-5p, miR-183-5p, and miR-9-3p. Cytokine analysis revealed IFN-γ, IL-17, IL-12A, IL-1β, and IL-6 overexpression, with IL-10 downregulation. Conclusions. Dynamic changes of miRNAs were observed over the course of EAAU. By initiating NF-κB signaling, the expressions of downstream cytokines and effector cells from the Th17 and Th1 lineages were sequentially activated, contributing to the disease.